Efecto del té de compost como control biológico al ataque del mildiu polvoso (Oidium sp.) en dos variedades susceptibles de rosa en la provincia de Cotopaxi – 2021. - Benavides Velasco, Luis Humberto (2022)
The present research was carried out in the Isinche neighborhood, Pujilí on the property of Eng. Holguer Tipán. The main objective was to determine the effect of compost tea on two varieties of rose susceptible to attack by powdery mildew (Oidium sp.) as a biological control alternative. The research was experimental and the inductive-deductive method was used. The varieties evaluated were Explorer and Mondial, the compost tea was made using compost from vegetable residues and was maintained with aeration using an oxygenation pump. The methodology was experimental; a randomized complete block design with a total of 6 treatments and four repetitions was used, the hypothesis tests were evaluated by Tukey at 5%. Data from 20 plants were taken at random for each treatment and the variables to be evaluated were the percentage of severity, the percentage of non-exportable flower due to Oidium sp. and the percentage of effectiveness of the applications. The results obtained confirmed that the chemical control presented the best averages for the two varieties, followed by compost tea at 20 mLL-1; and, finally, the economic analysis carried out revealed that the biological control obtained a lower cost than the chemical control, where the compost tea (20 mLL-1) presented a ha/month value of $235.2 and the results obtained referred to the severity, number of non-exportable stems and efficacy were satisfactory, with a difference of $100 less than the conventional control, which reached a value of $335.2.